Penerapan Strategi Pembelajaran Kontekstual pada Pembuatan Komik Mengaitkan Mata Pelajaran Matematika dengan Materi Kejuruan Tata Busana di SMK Negeri 3 Kudus - Luvita Nafisah; Godham Eko Saputro; Alfina Muzdalifah; Sofinatur Rohmah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Constructivism is knowledge created by humans and gradually developed in a limited environment, is the theoretical basis of contextual thinking (philosophy). A learning strategy known as contextual-based learning centers on giving students access to relevant and authentic environments. The main goal of this teaching is to help students better understand and apply information by having them make connections between the course material and their everyday experiences. This research tries to use contextual learning methodology in making comics that connect mathematics classes with fashion vocational resources at SMK Negeri 3 Kudus. There is much promise in contextual learning to support students in understanding and using mathematical ideas in their professional environments. The research method used is a qualitative method by conducting observations and interviews. Data was collected through observation, interviews, and analysis of student work. The research results show that the application of contextual learning strategies in making comics is effective in increasing students' understanding and interest in mathematics subjects and facilitating the application of mathematical concepts in the vocational context of fashion design.